The trilogy of China cotton markets: The lead–lag relationship among spot, forward, and futures markets. Issue 4 (14th December 2018) - Demir, Mert; Martell, Terrence F.; Wang, Jun
Abstract: China is a leading participant in the world cotton market. China's distinctive regulatory structure and procedures and business environment provide an opportunity to explore some unique market dynamics. This study investigates the interrelationship among the spot, futures, and forward cotton markets in China over a period of a major policy change: A temporary State reserve program for cotton that was established in 2011 and ended in 2014. This government intervention significantly distorted the way farmers, manufacturers, and speculators interacted and was not sustainable. Overall, our results support futures market's dominant role in the price discovery process.